Empathy-Based Pedagogy in Indonesian Bilingual Education: A Qualitative Case Study of Freedom Writers-Inspired Teaching Practices in Surakarta - Pamungkas, Damar Jati; Nugroho, Abdillah; Thoyibi, M. (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Bilingual education in Indonesia increasingly emphasizes both linguistic competence and character development, yet limited research examines how international pedagogical models can be adapted to local contexts. This qualitative case study investigates the implementation of empathy-based teaching approaches inspired by the film Freedom Writers (2007) in three bilingual schools in Surakarta, Indonesia. Data were collected over 2 months (October - November 2025) through classroom observations, teacher interviews, and student reflections. Thematic analysis revealed five key outcomes: transformed classroom atmospheres fostering student voice, enhanced language proficiency through reflective writing, strengthened critical thinking via culturally relevant curriculum, and improved socio-emotional competencies. Despite challenges including time constraints and cultural adaptation needs, findings demonstrate that empathetic, student-centered pedagogy significantly enhances both academic and character outcomes in bilingual settings. This study contributes empirical evidence for integrating transformative pedagogical approaches within Indonesian educational contexts while respecting local values and bilingual learning objectives.